Optimal economic statistical design of adaptive attribute control charts for monitoring three level products. Issue 5 (3rd September 2021) - Katebi, Mehdi; Rahim, Abdur
ABSTRACT: Three level control charts are used to monitor processes, where the quality of products is characterized by classifying the product characteristic into three discrete levels. Recent studies have approved the advantages of using adaptive schemes rather than static one in monitoring such processes. In this paper, we develop adaptive control charts for monitoring three level products from an economic statistical perspective. Using numerical examples, we illustrate the performance of the proposed models. A sensitivity analysis is also carried out to investigate the effects of model parameters on the solution of the economic design by using the design of experiments (DOE) technique and multiple linear regression analysis method.